Electrochemical skin conductance to assess peripheral neuropathy in rheumatic diseases with or without type 2 diabetes using sudoscan - Osama M. I. Mohamed; Nagwa M. M. Ali; Mohammed O. Ibrahim; Dana Sarmini; Farah Ibrahim; Mariam Al Hosany (Journal of Family Medicine and Primary Care)
Introduction: Peripheral neuropathy (PN) occurs in diabetes mellitus. However, the association between PN and rheumatic disease (RD) has not been fully investigated. The aim of this study was to assess the prevalence of PN in patients with RDs with or without Diabetes Mellitus. Methods: A Cross-sectional cohort study, data extracted from patients medical records started in September 2023 to January 2024 in Abu Dhabi, UAE. A Sudoscan machine report was used to assess The electrochemical skin conductance (ESC), Sudomotor dysfunction is evaluated according to the ESC measured on the feet: >60 μS = no dysfunction; 60–40 μS = moderate dysfunction; and <40 μS = severe dysfunction. Results: Eighty-one patients with RDs, mean age 58 ± 12. There were 55 females (67.9%), and 26 males (32.1%) attended an ambulatory healthcare clinic in Abu Dhabi, UAE. Thirty-three (40.7%) had diabetes, while 48 (59.3%) did not have diabetes. The mean glycated haemoglobin A1c (HBA1c) was 7.4% in diabetic patients and 5.8% in non-diabetic patients Additionally, all patients had a mean blood pressure of 134/72 and a mean Body Mass Index (BMI) of 31.40 kg/m2. Among the study patients, the most common RD was osteoarthritis, which affected 56.8% of the patients. The smallest percentage of patients with PN was found in those with IgG4, at 1.2%. The prevalence of Sudomotor dysfunction (ESC feet: <60 μS) was 72.8% in patients with RDs (all patients diabetic and non-diabetic), while the prevalence of sudomotor dysfunction (ESC feet: <60 μS) in RDs patients with diabetes was 75.8% and 70.8% in RDs patients without diabetes, there was no significant difference between in prevalence of sudomotor dysfunction in RD patients with diabetes compared to RD patients without Diabetes. Conclusion: Sudomotor dysfunction appears to be common among patients with RD regardless they have diabetes or not. This study recommends screening all RD patients for Sudomotor Dysfunction.